Considerations regarding the security influences of the covid19 pandemic on the public health field in Romania - Cătălin Peptan (THOT Publishing House, 2021)
Starting from the importance of the public health field in Romania's national security gear, the authors analyze the impact of the SARS-CoV-2 coronavirus on this field, highlighting some of the security consequences of the COVID-19 pandemic generated by the new coronavirus. The proposed analysis covers the period 28.02.2020-15.09.2021 and highlights the evolution of some statistical parameters representative for the description of the COVID-19 pandemic, such as: the number of cases of people infected with coronavirus (total cases, active cases, cured cases, deaths); testing dynamics and vaccination dynamics, including the adverse reactions that occurred during the vaccination process, in the context of the high degree of transmissibility and contagion of the coronavirus. The study highlights that Romania is on one of the last places in the European Union (EU) in terms of vaccination rate of the population, despite a campaign heavily publicized and supported by the authorities, determined by the spread in the public space of conspiracy theories regarding the origins of coronavirus and the side effects of vaccination on the population, in the context of the emergence of adverse reactions to the administration of certain types of vaccine. It is highlighted that the delay in obtaining mass immunization of the population has detrimental consequences on the health and for the evolution of social life in the next period.